THE ETYMOLOGY AND LINGUISTIC EXPRESSION OF THE CONCEPT OF “EDUCATION-UPBRINGING” (Scientific journal of the Fergana State University, 2025)
This study investigates the etymology and linguistic expression of the concept “education-upbringing” as represented in English and Uzbek languages, focusing on how these terms reflect distinct cultural values around knowledge and moral development. In English, “education” and “upbringing” are treated as separate domains, often associated with academic learning and personal development, respectively. In contrast, the Uzbek compound term “ta’lim-tarbiya” integrates these dimensions, embodying a holistic view of personal and academic growth rooted in a collectivist culture. This research uses comparative etymological and discourse analysis to trace the historical origins of each term and explore their contemporary linguistic representations in educational and social discourse. Findings reveal that cultural attitudes toward individualism and collectivism shape the linguistic and practical separation-or integration-of these concepts. The study concludes by discussing the implications for cross-cultural understanding of educational practices and suggests that examining similar concepts in other languages could deepen insights into the universal values underpinning education and moral instruction.